Determination of the Uptake of Ibuprofen, Ketoprofen, and Diclofenac by Tomatoes, Radishes, and Lettuce by Gas Chromatography–Mass Spectrometry (GC–MS). (22nd January 2021) - Kovacs, E. D.; Silaghi-Dumitrescu, L.; Kovacs, M. H.; Roman, C.
Abstract: The present study aimed to assess the uptake of the common nonsteroidal anti-inflammatories ibuprofen, ketoprofen and diclofenac by lettuce, radishes, and tomatoes. The influence of multiple routes of exposures (soil, water, vapor) of the pharmaceuticals were invstigated. The impact of accumulated pharmaceuticals active ingredients on the vegetable quality as the carbohydrate, amino acid, volatile organic aroma, and fatty acid methyl ester content were also investigated. The determination of the pharmaceutical active ingredients and vegetable quality compounds was performed by gas chromatography. For all of the vegetables, the diclofenac bioconcentration factor was the highest, as the concentration was between 31 and 118 ng·g −1 . Ibuprofen was easily accumulated in radishes and lettuce, with levels between 6 and 58 and 11 and 73 ng·g −1, respectively. Higher concentrations of the pharmaceutical active ingredients were determined when the soil was artificially contaminated. The average values of bioconcentration factors considering studied pharmaceuticals active ingredients were in the following order: diclofenac > ibuprofen > ketoprofen. Considering the impact upon the vegetable carbohydrate content, a decreasing tendency in percentage values was observed for the carbohydrate concentration in radishes and tomatoes treated by pharmaceuticals through contaminated soil and water. Similarly, the volatile organic aroma compounds decreased from 7% to 36% compared with the controls when the vegetables were cultivated in contaminated conditions.